Corrigendum to “Associations between multiple metals exposure and cognitive function in the middle-aged and older adults from China: A cross-sectional study” [Environ. Res., 263(Pt 1), 2024, 120038] - Shiru Hong; Sheng Wu; Zhengce Wan; Chenming Wang; Xin Guan; Ming Fu; Chenliang Liu; Tianhao Wu; Guorong Zhong; Yuhan Zhou; Yang Xiao; Yingqian You; et al. (Environmental Research, 2026)

Microbial insights into a high water-quality dependent freshwater snail: Geographical origin and rearing mode shape the gut antibiotic resistance gene profile of Sulcospira hainanensis - Lingtong Ye; Chen Chen; Shengli Fu; Jie Lu; Tuo Yao; Huajian Lin; Zhifu Liang; Huan Li; Jinxia Peng; Zhenhua Ma (Environmental Pollution, 2026)

Defect-engineered polyimide@TiO2-x skeleton with abundant oxygen vacancies regulating continuous Li+ transport pathways for advanced solid-state polymer electrolytes - Zhaoyi Wang; Bingxue Liu; Daolei Lin; Zheng Zhao; Guofeng Tian; Shengli Qi; Dezhen Wu (Chemical Engineering Journal, 2026)

Coral-inspired in situ immobilized lipase on covalent organic framework for efficient synthesis of flavor esters - Shengli Ding; Mengqi Wang; Guiqing Lin; Yanrong Song; Ji Zhang; Yufei Zhang; Mingming Zheng (Food Chemistry, 2026)

Constructing a highly conjugated polyarylimide framework delivering excellent cathodic stability for long-life organic lithium-ion batteries - Mohamed A. Elnaggar; Yongjun Kang; Daolei Lin; Zheng Zhao; Bingxue Liu; Guofeng Tian; Shengli Qi; Dezhen Wu (Chemical Engineering Journal, 2026)

Nearly “zero” shrinkage polyimide aerogel enabled by thiazine/imidazole in-situ co-catalyzed low-temperature imidization strategy for thermal insulation and electromagnetic transparency - Runyue Li; Daolei Lin; Zheng Zhao; Guofeng Tian; Shengli Qi; Dezhen Wu (Chemical Engineering Journal, 2026)

Cadmium exposure is associated with impaired ovarian function: Potential role of cadmium-induced ferroptosis in granulosa cells - Jing Li; Yutong Wang; Yali Huang; Nidong Li; Yingxin Zhu; Shengli Lin; Linlin Wang; Wei Guo; Lailai Yan; Chan Tian; Ying Wang (Journal of Hazardous Materials, 2026)

The Potential Implications of Neutrophil to Albumin Ratio for Short-term Prognosis in Myasthenia Gravis Patients - Hai Lin; Shenyi Lin; Shengli Pan; Shengqi Li; Jinrong Zhu; Yukai Wang; Siyao Chen; Lingsheng Wang; Zhangjing Zhu; Shiyue Wang; Suwen Huang; Yiyun Weng (Molecular Neurobiology, 2026)

Cerebral network topology and peak width of skeletonized mean diffusivity changes associated with cognitive impairment in patients with obstructive sleep apnea - Xiaoshan Lin; Shiwei Lin; Fajian Wei; Shengli Chen; Qunjun Liang; Shuo Li; Yingwei Qiu (Brain Imaging and Behavior, 2025)

Nitrogen fertilization management is required for soil phosphorus mobilization by phoD-harboring bacterial community assembly and pqqC-harboring bacterial keystone taxa - Lin YANG; Runze WANG; Jingwei SHI; Rui WANG; Shengli GUO (Pedosphere, 2025)

Passion fruit peel pectin improves glucose and lipid metabolism in high-fat diet-induced obesity through gut microbiota and insulin sensitivity regulation - Ying Ju; Liling Huang; Hailing Luo; Yongcai Huang; Xianya Huang; Ge Chen; Jie Gui; Shengli Lin; Xuzhou Liu; Liu Yang (Food Bioscience, 2025)

How many trees are there in China? - Kai Cheng; Haitao Yang; Yuling Chen; Zekun Yang; Yu Ren; Yixuan Zhang; Danyang Lin; Weiyan Liu; Guoran Huang; Jiachen Xu; Mengxi Chen; Zhiyong Qi; et al. (Science Bulletin, 2025)

FengYun-3 meteorological satellites’ microwave radiation Imagers enhance land surface temperature measurements across the diurnal cycle - Yuyang Xiong; Tianjie Zhao; Haishen Lü; Zhiqing Peng; Jingyao Zheng; Yu Bai; Panpan Yao; Peng Guo; Peilin Song; Zushuai Wei; Ronghan Xu; Shengli Wu; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Sustainable utilization of phosphorus-rich sludge in cement composites: Multiscale evaluation and mechanistic analysis - Shengli Ren; Zhirong Xu; Benqin Yang; Xiao-Yong Wang; Yi Han; Run-Sheng Lin; Yongpang Liao (Journal of Environmental Chemical Engineering, 2024)

Associations between multiple metals exposure and cognitive function in the middle-aged and older adults from China: A cross-sectional study - Shiru Hong; Sheng Wu; Zhengce Wan; Chenming Wang; Xin Guan; Ming Fu; Chenliang Liu; Tianhao Wu; Guorong Zhong; Yuhan Zhou; Yang Xiao; Yingqian You; et al. (Environmental Research, 2024)

Preparation of cementing material and recovery of iron resources using converter slag - Shuai Hao; Guoping Luo; Lin Wang; Shengli An; Yifan Chai; Wei Song (Process Safety and Environmental Protection, 2024)

The effect of concentration gradient on overpressure hazards and flame behavior of gas explosion in a vessel-duct connected device - Jifa Qian; Yuan Gao; Zhentang Liu; Song Lin; Zhoujie Gu; Hui Li; Shengli Kong (Fuel, 2024)

Binary-Network structured PI@SiO2 nanofibrous composite aerogels with temperature invariant superelasticity for thermal insulation - Qicheng Xue; Nanxi Dong; Peiqi Fan; Daolei Lin; Guofeng Tian; Jun Liu; Jiaming Wei; Shengli Qi; Dezhen Wu (Chemical Engineering Journal, 2024)

Self-supporting high-entropy Co-Cr-Fe-Ni-Nb oxide electrocatalyst with nanoporous structure for oxygen evolution reaction - Yuhan Lin; Wence Xu; Zhonghui Gao; Yanqin Liang; Hui Jiang; Zhaoyang Li; Shuilin Wu; Zhenduo Cui; Huaijun Sun; Huifang Zhang; Shengli Zhu (Chemical Engineering Journal, 2024)

Borneol serves as an adjuvant agent to promote the cellular uptake of curcumin for enhancing its photodynamic fungicidal efficacy against Candida albicans - Zhenlong Zhou; Shengli Wang; Penghui Fan; Xiaofeng Meng; Xinyu Cai; Wen Wang; Lin Ma; Hang Ma; Jianyu Su (Journal of Photochemistry and Photobiology B: Biology, 2024)

Transesterification of acidic palm oil using solid waste/CaO as a bifunctional catalyst - Jisen Liu; Tong Lin; Shengli Niu; Jie Zhu; Zihao Yang; Jie Geng; Sitong Liu; Yue Zheng; Bo Liang; Xiaobin Sun; Huaji Zhang (Fuel, 2024)

Differentiation of prokaryotic community composition in suspended sediment size-fractionation in a small loess watershed - Tongtong Li; Wei Zhang; Lin Yang; Shengli Guo; Rui Wang (CATENA, 2024)

Distinct variabilities of soil abundant and rare bacteria relate differently to carbon cycling functionality in eroded ecosystems - Lanlan Du; Shengli Guo; Rui Wang; Yanqing Guo; Yaxian Hu; Lin Yang; Weijia Li (CATENA, 2024)

Effects of microplastic properties and dissolved organic matter on phosphorus availability in soil and aqueous mediums - Runze Wang; Lin Yang; Miaomiao Guo; Xiaohua Lin; Rui Wang; Shengli Guo (Environmental Pollution, 2024)

Connectome architecture modulates the gray matter atrophy in major depression disorder patients with diverse suicidal ideations - Shengli Chen; Xiaojing Zhang; Shiwei Lin; Yingli Zhang; Ziyun Xu; Yanqing Li; Manxi Xu; Gangqiang Hou; Yingwei Qiu (Brain Imaging and Behavior, 2023)

Overcoming the fluorescent interference during Raman spectroscopy detection of microplastics - Yu Liu; Jiale Hu; Liqian Lin; Bing Yang; Minhua Huang; Min Chang; Xiaoxin Huang; Zhenqing Dai; Shengli Sun; Lei Ren; Chengyong Li (Science of The Total Environment, 2023)

High photocatalytic performance of ferroelectric AgNbO3 in a doping state - Lei Jiang; Xiaohua Huang; Yi Zhou; Shengli Huang; Yiwei Wang; Zijian Wang; Dong Sun; Hongyi Lin; Zaijun Cheng (Journal of Environmental Chemical Engineering, 2023)

A multilayer perceptron-based fast sunlight assessment for the conceptual design of residential neighborhoods under Chinese policy - Can Jiang; Xiong Liang; Yu-cheng Zhou; Yong Tian; Shengli Xu; Jia-Rui Lin; Zhiliang Ma; Shiji Yang; Hao Zhou (Building and Environment, 2023)

Investigation on bioactive metabolites produced by an endophytic fungus Trichoderma citrinoviride from the arils of Torreya grandis - Xiaohui Kong; Lin Xu; Xiaokang Ji; Shengli Yang; Hui Zhang (Natural Product Research, 2023)

Structural Characterization and Biological Activity of Oligopeptides from Isochrysis zhanjiangensis: Based on Quantum Mechanics, Molecular Docking and in Vitro Experiments - Liyuan Lin; Huijuan Li; Pengzhi Hong; Chunxia Zhou; Shengli Sun; Zhongji Qian (Journal of Ocean University of China, 2023)

Changes in fungal diversity and key-stone taxa along soil-eroding catena - Runze Wang; Lin Yang; Xin Gao; Shengli Guo; Rui Wang (Applied Soil Ecology, 2023)

Divergent responses of phoD- and pqqC-harbouring bacterial communities across soil aggregates to long fertilization practices - Lin Yang; Lanlan Du; Weijia Li; Rui Wang; Shengli Guo (Soil and Tillage Research, 2023)

Construction of Cordycepin High-Production Strain and Optimization of Culture Conditions - Hui Zhang; Ping Chen; Lin Xu; De Xu; Wendi Hu; Yong Cheng; Shengli Yang (Current Microbiology, 2023)

Phactr1 negatively regulates bone mass by inhibiting osteogenesis and promoting adipogenesis of BMSCs via RhoA/ROCK2 - Wei Lin; Zhipeng Chen; Xiaoyi Mo; Shengli Zhao; Zhenxing Wen; Wing Hoi Cheung; Dan Fu; Bailing Chen (Journal of Molecular Histology, 2022)

Simultaneous quantification of hepatic MRI-PDFF and R2* in a rabbit model with nonalcoholic fatty liver disease - Xiaomin Wang; Xiaojing Zhang; Lin Ma; Shengli Li (Science China Life Sciences, 2018)

Global environmental costs of China's thirst for milk - Zhaohai Bai; Michael R. F. Lee; Lin Ma; Stewart Ledgard; Oene Oenema; Gerard L. Velthof; Wenqi Ma; Mengchu Guo; Zhanqing Zhao; Sha Wei; Shengli Li; Xia Liu; et al. (Global Change Biology, 2018)
China has an ever‐increasing thirst for milk, with a predicted 3.2‐fold increase in demand by 2050 compared to the production level in 2010. What are the environmental implications of meeting this demand, and what is the preferred pathway? We addressed these questions by using a nexus approach, to examine the interdependencies of increasing milk consumption in China by 2050 and its global impacts, under different scenarios of domestic milk production and importation. Meeting China's milk demand in a business as usual scenario will increase global dairy‐related (China and the leading milk exporting regions) greenhouse gas ( GHG ) emissions by 35% (from 565 to 764 Tg CO 2eq ) and land use for dairy feed production by 32% (from 84 to 111 million ha) compared to 2010, while reactive nitrogen losses from the dairy sector will increase by 48% (from 3.6 to 5.4 Tg nitrogen). Producing all additional milk in China with current technology will greatly increase animal feed import; from 1.9 to 8.5 Tg for concentrates and from 1.0 to 6.2 Tg for forage (alfalfa). In addition, it will increase domestic dairy related GHG emissions by 2.2 times compared to 2010 levels. Importing the extra milk will transfer the environmental burden from China to milk exporting countries; current dairy exporting countries may be unable to produce all additional milk due to physical limitations or environmental preferences/legislation. For example, the farmland area for cattle‐feed production in New Zealand would have to increase by more than 57% (1.3 million ha) and that in Europe by more than 39% (15 million ha), while GHG emissions and nitrogen losses would increase roughly proportionally with the increase of farmland in both regions. We propose that a more sustainable dairy future will rely on high milk demanding regions (such as China) improving their domestic milk and feed production efficiencies up to the level of leading milk producing countries. This will decrease the global dairy related GHG emissions and land use by 12% (90 Tg CO 2eq reduction) and 30% (34 million ha land reduction) compared to the business as usual scenario, respectively. However, this still represents an increase in total GHG emissions of 19% whereas land use will decrease by 8% when compared with 2010 levels, respectively.

Expression Profile of MiR-128 in the Astrocytoma Patients and Cell Lines - Jingjing Xu; Yuqiong Liu; Si Guo; Shengli Ma; Lin Xiao; Na Wei; Rui Xue (Molecular Neurobiology, 2016)

Serum Uric Acid Levels and Outcomes After Acute Ischemic Stroke - Zhongchao Wang; Yanlin Lin; Yuxiu Liu; Ying Chen; Bin Wang; Changgui Li; Shengli Yan; Yangang Wang; Wenjuan Zhao (Molecular Neurobiology, 2016)

Spatial and temporal variations of global frictional torque during the period 1948–2011 - He Gong; Mei Huang; Lin Zhu; Shengli Guo; Yaping Shao (Journal of Meteorological Research, 2016)

Multiparameter cluster analysis of seasonal variation of water masses in the eastern Beibu Gulf - Shengli Chen; Yan Li; Jianyu Hu; Airong Zheng; Lingfeng Huang; Yuanshao Lin (Journal of Oceanography, 2011)